Gestational diabetes - management strategies including pharmacological treatment and lifestyle interventions - Adrianna Skóra; Katarzyna Hajduk-Maślak; Iwona Galasińska; Beniamin Michalik; Aleksandra Szypuła; Michał Sęk (Kazimierz Wielki University, 2024)
Diabetes is a chronic disease, characterized by elevated blood glucose levels, resulting from insulin resistance and inadequate insulin production. Among many types of diabetes, gestational diabetes (GDM) is a unique kind, correlated with numerous metabolic changes occurring during pregnancy, it develops around second  trimester of the gestation and in most cases resolves after delivery.  The prevalence of gestational diabetes is rising globally and becomes a significant public health concern. [48] According to the World's Health Organization's classification GDM is, apart from the diabetes mellitus type 1 (DM1)  and diabetes mellitus type 2 (DM2), one of the main clinical forms of carbohydrate metabolism disorders occurring during pregnancy. So far, epidemiological data are ambiguous regarding GDM prevalence, this study estimates GDM frequency at 4-12%. [1] The aim of this article is to provide a comprehensive analysis of the topic of gestational diabetes, its prevalence, risk factors, importance of early detection, methods of glycemia monitoring and management strategies, including lifestyle interventions and pharmacological treatment.  Referring to the treatment, it also describes the preparation for pregnancy of people with preexisting DM1 and DM2 and the necessity to modify foregoing management strategies. Furthermore, it describes the most frequent early complications resulting from GDM as well as long-term outcomes for both mother and offspring.